Gums and stabilisers for the food industry. 17, - Williams, Peter A.; Phillips, Glyn O. (Royal Society of Chemistry, 2014)
The book describes the new advances in the science and technology of hydrocolloids which are used in food and related systems. The focus is on the technofunctionality and the biofunctionality of hydrocolloids, giving an appropriate emphasis to the manipulative skills of the food scientist and recognising the special part hydrocolloids can play in supporting human health. Gums and Stabilisers for the Food Industry 17 captures the latest research findings of leading scientists which were presented at the Gums and Stabilisers for the Food Industry Conference. Covering a wide range of topics, including; functional properties of proteins, alternative protein surces, low moisture foods, value added co-products from biorefining and bioactive polysaccharides. This book will be a useful information source to researchers and other professionals in industry and academia, particularly those involved with food science.
Includes index.
Keywords: Hydrocolloids.; Food industry and trade.; elektronické knihy; electronic books